Current and upcoming development in basic research of measurable, controllable and manageable IP network - MENG Luo-ming1; XIE Gao-gang2; QIU Xue-song1; LI Hui 3; LONG Ke-ping4; YANG Yi-xian1; ZENG Lie-guang5 (Tongxin xuebao)
International program in science for measurable, controllable and manageable IP network was introduced, the research progress on measurable, controllable and manageable IP network was given, the prospect including network measurement, network management, network control was discussed. After analyzed of the prospect, a method studied measurable, controllable and manageable IP network was proposed. In this method, IP network and environment of IP network was studied as a entity. Two type of boundary condition including the boundary condition between IP network and service （application ）, the boundary condition between IP network and optical transport network was given.